An ethical framework for the creation, governance and evaluation of accelerated access programs. Issue 9 (September 2018) - Pace, Jessica; Ghinea, Narcyz; Kerridge, Ian; Lipworth, Wendy
Highlights: A model to conceptualise ethical and policy issues raised by accelerated access initiatives is proposed. A set of ethical principles to and guiding questions for policy makers is presented. Enables policy makers to attend systematically to various ethical and policy issues raised. Can assist policy makers to target initiatives to areas of greatest concern in their particular context. Abstract: There are increasing demands on regulators and insurers internationally to provide access to medicines more quickly, and often on the basis of less robust evidence of safety, efficacy or cost-effectiveness than have traditionally been required. These demands arise from a number of sources, including those advocating for access to medicines for patients with life-threatening diseases, rare diseases, or subsets of common diseases and where entire populations are threatened in the context of public health emergencies. In response to these demands, policymakers have instituted a number of initiatives aimed at speeding up access to medicines, which we refer to collectively as "accelerated access" programs. While there are strong arguments for accelerated access programs, these programs also raise a number of socio-political, epistemic and moral issues. Some of these issues are common to all types of accelerated access programs, while others are specific to particular types of accelerated access. Here, we offer a conceptual framework that highlights ethically relevant similarities and differences among different kinds of accelerated access processes for the purpose of enabling ethically and politically-informed policy making.